TÁRSADALMI, GAZDASÁGI ÉS TERÜLETI KOHÉZIÓ A XXI. SZÁZAD KELET-KÖZÉP-EURÓPÁJÁBAN - Szabó, Pál; György, Kukely; Gergely, Bártfai (Közép-Európai Közlemények, 2019)
As a result of their common economic and social problems, the post-socialist countries were similar in many ways and shared the same interests. Later on however these countries started to diverge due to the different resources and their usage, their different foreign policy and internal affairs, as well as the devaluation and revaluation of the local and location factors. The purpose of this study is to find out to what extent could the Visegrad Group (Poland, Czech Republic, Slovakia, Hungary) and Romania, Bulgaria be considered unified and/or split in terms of their social, economic and territorial aspects and problems. The similarities and differences of these countries are based on statistical database (source: Eurostat and Worldbank) which is built upon twenty social, economic and environmental indicators of the EU2020 targets and ten indicators linked to the territorial cohesion according to the Territorial Agenda. The results indicate that the differences and the ways of changing of the social and economic fields among the analyzed countries are diverse, hence the heterogeneity is indeed more intense but a stronger cohesion in the social dimension can be noticed. The common dimension of Central and Eastern Europe still prevail somewhat more about the indicators of the territorial cohesion despite the sharp differences in physical and social geography. All of these are worth paying attention to the upcoming discussion of the new EU budget period.